Preparation method of uniform and compact alcohol-permselective composite membrane
The preferred alcohol permeable composite film prepared by the gas-solid/gas-liquid interface reaction method solves the problems of uneven film formation and the use of toxic solvents in traditional methods, and achieves an efficient and environmentally friendly ethanol recovery effect.
Patent Information
- Application Number
- CN202411514040.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The traditional method of preparing a vaporized film with priority permeable alcohol permeable vaporization film has problems such as uneven film formation, poor density, and the use of toxic solvents, which affects the separation effect and environmental safety of the film.
By adopting the gas-solid/gas-liquid interface reaction method, a uniform and dense preferentially permeable composite film is prepared by cross-linking reaction between a gas-phase cross-linking agent and a solid-phase/liquid organic matter on the surface of the film. This method does not require the use of toxic solvents, and the crosslinking reaction is more complete and uniform.
The uniform and dense film formation of the film is achieved, the permeability and separation performance of the film are improved, the pollution to the environment is reduced, and the efficient recovery of ethanol is promoted.
Smart Images

Figure HDA0005106214240000011 
Figure HDA0005106214240000012 
Figure HDA0005106214240000013
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane separation and technology, and in particular relates to a uniform and dense composite membrane with preferential alcohol permeability and a preparation method thereof. Technical Background
[0002] In the production process of bioethanol, the low concentration of the fermentation liquid leads to a high separation cost of ethanol. The pervaporation technology based on membrane separation has the characteristics of low energy consumption, high selectivity and mild operating conditions, and can be coupled with the fermentation process to achieve efficient separation operation. In the fermentation-coupling process, it is necessary to remove the ethanol produced by fermentation in time to reduce the toxic effects on microorganisms and ensure rapid and continuous production. Therefore, the core of pervaporation is the selection of membrane materials and the preparation of membranes. The composite membrane with preferential alcohol permeation prepared by doping graphyne into organic polymers takes into account the advantages of graphyne's high permeability, high selectivity, high stability and easy processing of organic matter. Its application in the pervaporation operation process can effectively improve the recovery yield of ethanol.
[0003] The preparation methods of the conventional pervaporation membranes that preferentially permeate alcohols, such as the blade coating method and the dipping method, etc., have a solvent volatilization step in the process, which makes the cross-linking reaction of the organic polymer and the cross-linking agent insufficient, resulting in uneven film formation and poor compactness; in addition, the conventional film-making method uses a high molecular organic polymer with a large viscosity as the cross-linking main body to obtain a dense separation layer that preferentially permeates alcohols. Therefore, a large amount of toxic organic solvents (n-heptane, n-hexane, toluene, dimethylformamide, etc.) are required to dissolve the high molecular polymer in order to reduce the viscosity for film-forming operation. The volatilization of organic solvents into the air during the film-making process will cause pollution to the environment. In the preparation process of conventional composite membranes, the incompatibility of nanoparticles and polymers easily makes the nanoparticles unevenly distributed, resulting in effects such as particle agglomeration, thus affecting the separation effect of the composite membrane.
[0004] The gas-solid / gas-liquid interface reaction is to heat the substance that can undergo cross-linking reaction with the organic polymer into the gas phase, and then put the membrane loaded with graphyne and organic polymer into the gas phase environment, and the cross-linking reaction between the gas phase cross-linking agent and the solid phase / liquid phase organic matter occurs on the membrane surface to obtain a dense separation membrane. In this process, there is no solvent, the gas phase cross-linking agent can fully contact with the organic polymer, the reaction contact area is larger and more uniform, the reaction is more sufficient, and the film formation can be made denser. In this process, due to the more sufficient cross-linking, the thinner separation layer can play a highly selective role, the thickness of the composite membrane is reduced, and the permeability is improved. In summary, the method of gas-solid / gas-liquid interface reaction can obtain a composite membrane with high selectivity and high permeability. The dense film formation process can prepare a high-performance, defect-free pervaporation membrane for rapid and efficient separation of ethanol from aqueous solution, further promoting the industrial application of pervaporation preferential alcohol permeation composite membrane, which has high value in alcohol-water separation. Summary of the invention
[0005] The key technical problem to be solved by the present invention is to provide a method for preparing a uniform and dense composite membrane with preferential alcohol permeation, so as to further improve the performance of the membrane with preferential alcohol permeation in ethanol recovery. The specific technical scheme is as follows:
[0006] A method for preparing a uniform, dense, preferentially alcohol-permeable composite membrane comprises the following steps:
[0007] Step a, adding catalyst A containing copper ion compound to ethanol and mixing evenly, then adding monomer and organic polymer corresponding to synthetic graphyne thereto, stirring for 0.5-2h, ultrasonicating for 0.1-2h, then placing in a 50-150°C oven and heating for 2-10h to prepare graphyne / organic polymer membrane liquid A; loading membrane liquid A on a porous base membrane by a certain method, and then placing in the air to volatilize the solvent;
[0008] Step b, mixing the silicon-based crosslinking agent and catalyst B in a certain proportion, stirring for 0.1-2h, and preparing a membrane liquid B;
[0009] Step c, taking a certain amount of membrane liquid B and placing it at the bottom of the container, heating it to 40-100°C to fill the container with the crosslinking agent vapor, placing the porous base membrane loaded with graphyne / organic matter in step a in the vapor of the container, and allowing a gas-solid or / and gas-liquid reaction of the organic matter and the crosslinking agent to occur on the surface of the membrane, and the reaction time is 3-8 hours; then taking out the membrane and placing it in an environment of 80°C for 0.5-8 hours for further thermal crosslinking reaction.
[0010] Specifically, the graphyne described in step a is one or more of graphdiyne (GDY). Preferably, the monomer corresponding to the synthesis of the above-mentioned graphyne is one or more of 1,3,5-triethynylbenzene (TEB), tri(4-ethynylphenyl)amine (TEPA), 1,3,5-tri-(4-ethynylphenyl)benzene (Ext-TEB) or hexaethynylbenzene (HEB) containing terminal alkynes; catalyst A is one or more of copper hydroxide (Cu(OH)2) or copper acetate (Cu(CH3COO)2). The organic polymer is one or more of polydimethylsiloxane (PDMS), polyphenylmethylsiloxane (PPMS), polytrifluoropropylmethylsiloxane (PTFMS) or polytrimethylsilyl propyne (PTMSP).
[0011] Specifically, the porous base membrane described in step a is an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and the average pore size is 10-100 nm; the shape of the porous base membrane is flat, tubular or hollow fiber.
[0012] Specifically, the content of organic polymer in the membrane solution A in step a is 5wt%-80wt%, the content of graphyne synthesis monomer is 0.1wt%-20wt%, and the concentration of the catalyst A added to ethanol is 0.1-5g / L.
[0013] Preferably, the method for loading the membrane liquid A on the porous base membrane in step a is one or more of an immersion method, a vacuum filtration method, a spraying method, a spin coating method, and a blade coating method.
[0014] Specifically, the crosslinking agent described in step b is one or more of tetraethyl orthosilicate (TEOS), propyl orthosilicate (TPOS), butyl silicate (TBOS), vinyl triethoxysilane (VTES), ethyl triethoxysilane (ETES) or trifluoropropyl triethoxysilane (TFPTES); the catalyst is one or more of dibutyltin dilaurate (DBTDL), monobutyltin oxide (MBTO), dibutyltin oxide (DBTO), tripropyltin oxide (TPTO) or chloroplatinic acid.
[0015] Preferably, the content of the cross-linking agent in the membrane solution in step b is 80wt%-99wt%, and the content of the catalyst B is 1wt%-20wt%.
[0016] The invention is used for the application of uniform and dense composite membrane with preferential alcohol permeation, and separates ethanol from aqueous solution in the form of pervaporation.
[0017] The technical solution provided by the present invention has the following beneficial effects: the present invention adopts a gas-solid / gas-liquid interface reaction method to realize the cross-linking film formation of the polymer, so that the film formation is more uniform and sufficient, and the ethanol in the alcohol-water mixture is recovered by pervaporation. The film forming method used in the present invention can effectively increase the contact area between the crosslinking agent and the organic polymer, and the gas phase crosslinking agent can contact and react with the organic polymer more fully and uniformly. The crosslinking density of the film prepared by the gas-solid / gas-liquid interface reaction in the present invention is 21.3×10 -4 mol cm -3 , the cross-linking density of the membrane prepared by the traditional method is higher ( Figure 1 ), which can make the cross-linking of the effective separation layer polymer more compact, the bonding force of the membrane layer is stronger, and the membrane separation performance is increased. The thickness of the effective separation layer of the membrane prepared by the present invention is 1-3μm, which is more than 70% lower than that of the traditional membrane making method ( Figure 2 ), can effectively enhance the permeability, the membrane permeation flux is 2-3 times that of the traditional composite membrane. In addition, the method of the present invention does not use toxic solvents, the membrane is dense and uniform, and lays the foundation for the efficient separation of alcohol-water mixtures by preferential alcohol permeation composite membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1.Comparison chart of the crosslinking density of the pure PDMS membrane prepared by the gas-solid interface reaction method in Example 1 of the present invention and the pure PDMS membrane prepared by the traditional method.
[0019] Figure 2 . Pure PDMS membrane prepared by gas-solid interface reaction method in Example 1 of the present invention ( Figure 2-1 ) and the pure PDMS membrane prepared by the traditional method ( Figure 2-2 )’s thickness comparison diagram obtained by EDS line scan energy spectrum.
[0020] Figure 3 .Scanning electron microscope images of the (3-1) surface and (3-2) cross section of the TNP-GDY / PDMS composite membrane prepared in Example 2 of the present invention.
[0021] Figure 4 .Scanning electron microscope images of the (4-1) surface and (4-2) cross section of the TNP-GDY / PDMS composite membrane prepared in Example 4 of the present invention.
[0022] Figure 5 .Scanning electron microscope images of the (5-1) surface and (5-2) cross section of the HsGDY / PDMS composite membrane prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the present invention clearer, the embodiments of the present invention will be further described in detail below in conjunction with the accompanying drawings, but the present invention is not limited to the following examples. The cross-linking density test is measured using a VTMR20-010V-I nuclear magnetic resonance cross-linking density imaging analyzer, the scanning electron microscope surface image and cross-sectional image are observed and measured using a ZEISS Sigma 300 scanning electron microscope (SEM), and the thickness of the film is measured by Xplore energy dispersive X-ray spectroscopy (EDS) for corresponding elemental analysis.
[0024] The embodiment of the present invention provides a method for preparing a uniform and dense composite membrane with preferential alcohol permeability, comprising the following steps:
[0025] Step 101, adding catalyst A containing copper ion compound into ethanol to prepare a 0.5 g / L solution, then adding monomers and organic polymers corresponding to synthetic graphyne thereto, stirring for 1 hour, ultrasonicating for 0.5 hour, then placing in a 60-120° C. oven and heating for 2-10 hours to prepare graphyne / organic polymer membrane liquid A. The porous base membrane is loaded with membrane liquid A by a certain method, and then placed in the air to volatilize the solvent for 2 hours.
[0026] Step 102: Evenly mix the silicon-based crosslinking agent and catalyst B in a certain proportion, stir for 0.5 h, and prepare membrane liquid B.
[0027] Step 103: Take a certain amount of membrane liquid B and place it at the bottom of the container, heat it to 40-80°C to fill the container with the crosslinking agent vapor, place the porous base membrane loaded with graphyne / organic matter in step 101 in the container, and react the organic matter and the crosslinking agent on the membrane surface for 3-8 hours. Then, place the membrane in an environment of 80°C for 0.5-8 hours to further perform a thermal crosslinking reaction.
[0028] Specifically, the graphyne described in step 101 is one or more of graphdiynes (GDY). The graphyne monomer is one or more of 1,3,5-triethynylbenzene (TEB), tris(4-ethynylphenyl)amine (TEPA), 1,3,5-tris-(4-ethynylphenyl)benzene (Ext-TEB) or hexaethynylbenzene (HEB) containing terminal alkynes; catalyst A is one or more of copper hydroxide (Cu(OH)2) or copper acetate (Cu(CH3COO)2). The organic polymer is one or more of polydimethylsiloxane (PDMS), polyphenylmethylsiloxane (PPMS), polytrifluoropropylmethylsiloxane (PTFMS) or polytrimethylsilyl propyne (PTMSP).
[0029] Specifically, the porous base membrane in step 101 is an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and the average pore size is 10-100 nm; the shape of the porous base membrane is flat, tubular or hollow fiber.
[0030] Specifically, the content of organic polymer in the membrane liquid A in step 101 can be 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, or 50wt%; the content of graphyne synthesis monomer can be 0.5wt%, 1wt%, 2wt%, 3wt%, or 4wt%; and the concentration of the solution of catalyst A added to ethanol can be 0.1g / L, 0.5g / L, 1g / L, 3g / L, or 5g / L.
[0031] Preferably, the method for loading the membrane liquid A on the porous base membrane in step 101 is one or more of an immersion method, a vacuum filtration method, a spraying method, a spin coating method, and a scraping method.
[0032] Specifically, the crosslinking agent described in step 102 is one or more of tetraethyl orthosilicate (TEOS), propyl orthosilicate (TPOS), butyl silicate (TBOS), vinyl triethoxysilane (VTES), ethyl triethoxysilane (ETES) or trifluoropropyl triethoxysilane (TFPTES); the catalyst B is one or more of dibutyltin dilaurate (DBTDL), monobutyltin oxide (MBTO), dibutyltin oxide (DBTO), tripropyltin oxide (TPTO) or chloroplatinic acid.
[0033] Preferably, the content of the cross-linking agent in the membrane liquid in step 102 may be 80wt%, 85wt%, 90wt%, or 95wt%, and the content of the catalyst B may be 5wt%, 10wt%, 15wt%, or 20wt%.
[0034] Preferably, the vaporization heating temperature of the cross-linking agent in step 103 can be 40°C, 50°C, 60°C, 70°C, or 80°C; the cross-linking reaction time of the organic matter and the cross-linking agent can be 2h, 4h, 6h, 8h, or 10h; and the thermal cross-linking reaction time can be 2h, 4h, 6h, 8h, or 10h.
[0035] The present invention will be further described below through specific examples.
[0036] In the following specific examples, the operations involved, if the conditions are not specified, are all carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials used, if the manufacturers and specifications are not specified, are all conventional products that can be obtained from the market.
[0037] Example 1 (Comparative Example)
[0038] This example is a comparative experiment of pure polymer membrane.
[0039] A polysulfone (PSf) flat ultrafiltration membrane is used as a porous base membrane with a molecular weight cutoff of 20,000. The organic polymer is polydimethylsiloxane (PDMS), the crosslinking agent is tetraethyl orthosilicate (TEOS), and the catalyst B is dibutyltin dilaurate (DBTDL).
[0040] The gas-solid interface reaction film forming step is to add PDMS to the ethanol solution, stir at room temperature for 30 minutes, and prepare a PDMS solution with a PDMS content of 20wt%. The PDMS solution is added dropwise to the surface of the polysulfone-based membrane. After the solvent evaporates, the membrane is placed in a 50°C TEOS vapor environment (TEOS: DBTDL mass ratio is 8:1) for 6 hours, and then placed in a 80°C vacuum drying oven for cross-linking reaction for 8 hours. A uniform and dense pure PDMS preferentially permeable alcohol membrane is obtained.
[0041] The conventional method of film formation steps is to add PDMS, TEOS, and DBTDL to ethanol at a mass ratio of 8:1.2:0.15, stir at room temperature for 30 minutes, and prepare a PDMS cross-linking solution. The PDMS content in the solution is 20wt%, and the solution is added dropwise to the surface of the polysulfone base membrane. After the solvent evaporates, the solution is placed in a vacuum drying oven at 80°C for cross-linking reaction for 8 hours. A pure PDMS preferentially permeates alcohol membrane.
[0042] Figure 1The cross-linking density of the pure PDMS film prepared by the gas-solid interface reaction method in this example is greater than that of the film prepared by the traditional method, indicating that the gas-solid interface reaction method can make the film more uniform and dense. EDS line scan results ( Figure 2 ) showed that the thickness of the membrane prepared by the gas-solid interface reaction method was 2.5 μm, which was smaller than the membrane prepared by the traditional method (10 μm). This indicates that the use of the gas-solid interface reaction method to prepare membranes can reduce the thickness of the separation layer and thus increase the permeability of the membrane.
[0043] The prepared PDMS membrane was placed in a pervaporation device for performance testing. The test conditions were: (1) the raw material liquid composition was 5 wt % ethanol aqueous solution, and the feed temperature was 60° C.; (2) the membrane downstream pressure was 200 Pa.
[0044] The pervaporation performance of the pure PDMS membrane prepared by the gas-solid interface reaction method was measured as follows: the permeation flux was 3168.8 gm -2 h -1 , the separation factor is 8.8, and the ethanol content in the permeate is 30wt%. The pervaporation performance of the pure PDMS membrane prepared by the traditional method is measured as follows: the permeation flux is 1129.9gm -2 h -1 , the separation factor is 8.8, and the ethanol content in the permeate is 30wt%.
[0045] Example 2
[0046] A polysulfone (PSf) flat ultrafiltration membrane is used as a porous base membrane with a molecular weight cutoff of 20,000. The selected graphyne monomer is tri(4-ethynylphenyl)amine (TEPA), the catalyst A is copper acetate, wherein the copper acetate is dissolved in ethanol to form a 0.5 g / L solution, the selected organic polymer is polydimethylsiloxane (PDMS), the selected cross-linking agent is tetraethyl orthosilicate (TEOS), the selected catalyst B is dibutyltin dilaurate (DBTDL), and the selected organic solvent is ethanol.
[0047] Step a, dissolve the monomer tri(4-ethynylphenyl)amine (TEPA) and polydimethylsiloxane (PDMS) in a 0.5g / L copper acetate ethanol solution (mass ratio of 0.1:4:15.9), mix well, wherein the content of TEPA is 0.5wt%, and the content of polymer PDMS is 20wt%. Stir for 1h, ultrasonic for 0.5h, then place in a 60°C oven and heat for 6h to form TNP-GDY / PDMS membrane solution A. Immerse the polysulfone-based membrane in membrane solution A for 30s and 1 layer. Then place it in the air to volatilize the solvent for 2h, at which time there are only PDMS and TNP-GDY on the membrane, and the content of TNP-GDY is 2.5wt%.
[0048] Step b: mix the crosslinking agent tetraethyl orthosilicate (TEOS) and the catalyst B dibutyltin dilaurate (DBTDL) in a mass ratio of 8:1, stir for 0.5h, and prepare membrane liquid B.
[0049] Step c, taking a certain amount of membrane liquid B and placing it at the bottom of a container, heating it to 50°C so that TEOS vapor fills the container, placing the membrane loaded with TNP-GDY / PDMS in step a in the container, and reacting the organic matter and the crosslinking agent on the membrane surface for 6 hours. Then, placing the membrane in an environment of 80°C for 2 hours for thermal crosslinking reaction, and obtaining a TNP-GDY / PDMS pervaporation membrane that preferentially permeates alcohol.
[0050] SEM results ( Figure 3-1 ) shows that the Graphene loading on the surface of the prepared composite membrane is uniform. Figure 3-2 It shows that the thickness of the selective separation layer of the prepared composite membrane is 1 μm.
[0051] The prepared composite membrane was placed in a pervaporation device for performance testing. The test conditions were as follows: (1) the raw material liquid composition was 5 wt% ethanol aqueous solution, and the feed temperature was 60° C.; (2) the membrane downstream pressure was 200 Pa.
[0052] The pervaporation performance of the composite membrane was measured as follows: the permeation flux was 2196.2 gm -2 h -1 , the separation factor is 11.3, and the ethanol content in the permeate is 35wt%.
[0053] Example 3
[0054] Step a, dissolve the monomer tri(4-ethynylphenyl)amine (TEPA) and polydimethylsiloxane (PDMS) in a 0.5g / L copper acetate ethanol solution (mass ratio of 0.1:4:15.9) and mix evenly, wherein the content of TEPA is 0.5wt%, and the content of polymer PDMS is 20wt%. Stir for 1h, ultrasonicate for 0.5h, then place in a 60°C oven and heat for 6h to form TNP-GDY / PDMS membrane solution A. Immerse the polysulfone-based membrane in membrane solution A for 30s and 1 layer. Then place it in the air to volatilize the solvent for 2h, at which time there are only PDMS and TNP-GDY on the membrane, and the content of TNP-GDY is 2.5wt%.
[0055] Step b: mix the crosslinking agent tetraethyl orthosilicate (TEOS) and the catalyst B dibutyltin dilaurate (DBTDL) in a mass ratio of 8:1, stir for 0.5h, and prepare membrane liquid B.
[0056] Step c, taking a certain amount of membrane liquid B and placing it at the bottom of a container, heating it to 50°C so that TEOS vapor fills the container, placing the membrane loaded with TNP-GDY / PDMS in step a in the container, and reacting the organic matter and the crosslinking agent on the membrane surface for 4 hours. Then, placing the membrane in an environment of 80°C for 2 hours for thermal crosslinking reaction, and obtaining a TNP-GDY / PDMS preferential alcohol permeation vaporization membrane.
[0057] The prepared composite membrane was placed in a pervaporation device for performance testing. The test conditions were as follows: (1) the raw material liquid composition was 5 wt% ethanol aqueous solution, and the feed temperature was 60° C.; (2) the membrane downstream pressure was 200 Pa.
[0058] The pervaporation performance of the composite membrane was measured as follows: the permeation flux was 1898.1 gm -2 h -1 , the separation factor is 10.7, and the ethanol content in the permeate is 34wt%.
[0059] Example 4
[0060] Step a, dissolving the monomer tri(4-ethynylphenyl)amine (TEPA) and polydimethylsiloxane (PDMS) in a 0.5 g / L copper acetate ethanol solution (mass ratio of 0.1:4:15.9) and mixing evenly, wherein the content of TEPA is 0.5wt%, and the content of polymer PDMS is 20wt%. Stirring for 1 h, ultrasonication for 0.5 h, then placing in a 60 ° C oven for heating for 6 h, and configuring TNP-GDY / PDMS membrane liquid A. The membrane liquid A is loaded on a polysulfone-based membrane by vacuum filtration, and then placed in the air to volatilize the solvent for 2 h. At this time, only PDMS and TNP-GDY are on the membrane, and the content of TNP-GDY is 2.5wt%.
[0061] Step b: mix the crosslinking agent tetraethyl orthosilicate (TEOS) and the catalyst B dibutyltin dilaurate (DBTDL) in a mass ratio of 8:1, stir for 0.5h, and prepare membrane liquid B.
[0062] Step c, taking a certain amount of membrane liquid B and placing it at the bottom of a container, heating it to 50°C so that TEOS vapor fills the container, placing the membrane loaded with TNP-GDY / PDMS in step a in the container, and reacting the organic matter and the crosslinking agent on the membrane surface for 6 hours. Then, placing the membrane in an environment of 80°C for 2 hours for thermal crosslinking reaction, and obtaining a TNP-GDY / PDMS pervaporation membrane that preferentially permeates alcohol.
[0063] SEM results ( Figure 4-1 ) shows that the Graphene loading on the surface of the prepared composite membrane is uniform. Figure 4-2 It shows that the thickness of the selective separation layer of the prepared composite membrane is 2.5 μm.
[0064] The prepared composite membrane was placed in a pervaporation device for performance testing. The test conditions were as follows: (1) the raw material liquid composition was 5 wt% ethanol aqueous solution, and the feed temperature was 60° C.; (2) the membrane downstream pressure was 200 Pa.
[0065] The pervaporation performance of the composite membrane was measured as follows: the permeation flux was 4291.7 gm -2 h -1 , the separation factor is 9.0, and the ethanol content in the permeate is 30wt%.
[0066] Example 5
[0067] A polysulfone (PSf) flat ultrafiltration membrane is used as a porous base membrane with a molecular weight cutoff of 20,000. The graphyne monomer is 1,3,5-triethynylbenzene (TEB), and the catalyst A is cupric acetate, wherein the catalyst is dissolved in ethanol to form a 0.5 g / L solution. The organic polymer is polydimethylsiloxane (PDMS), the cross-linking agent is tetraethyl orthosilicate (TEOS), and the catalyst B is dibutyltin dilaurate (DBTDL).
[0068] Step a, dissolve the monomer 1,3,5-triethynylbenzene (TEB) and polydimethylsiloxane (PDMS) in a 0.5 g / L copper acetate ethanol solution (mass ratio of 0.1:4:15.9) and mix them evenly, wherein the content of TEB is 0.5wt%, and the content of polymer PDMS is 20wt%. Stir for 1 hour, ultrasonicate for 0.5 hour, and then place in a 60°C oven for 6 hours to prepare HsGDY / PDMS membrane liquid A. The membrane liquid A is loaded on a polysulfone-based membrane by vacuum filtration, and then placed in the air to volatilize the solvent for 2 hours. At this time, only PDMS and HsGDY are on the membrane, and the content of HsGDY is 2.5wt%.
[0069] Step b: mix the crosslinking agent tetraethyl orthosilicate (TEOS) and the catalyst B dibutyltin dilaurate (DBTDL) in a mass ratio of 8:1, stir for 0.5h, and prepare membrane liquid B.
[0070] Step c, taking a certain amount of membrane liquid B and placing it at the bottom of the container, heating it to 50°C so that TEOS vapor fills the container, placing the membrane loaded with HsGDY / PDMS in step a in the container, and reacting the organic matter and the crosslinking agent on the membrane surface for 6 hours. Then, placing the membrane in an environment of 80°C for 8 hours for thermal crosslinking reaction, and obtaining a HsGDY / PDMS pervaporation membrane with preferential alcohol permeation.
[0071] SEM results ( Figure 5-1 ) shows that the Graphene loading on the surface of the prepared composite membrane is uniform. Figure 5-2It shows that the thickness of the selective separation layer of the prepared composite membrane is 3 μm.
[0072] The prepared composite membrane was placed in a pervaporation device for performance testing. The test conditions were as follows: (1) the raw material liquid composition was 5 wt% ethanol aqueous solution, and the feed temperature was 60° C.; (2) the membrane downstream pressure was 200 Pa.
[0073] The pervaporation performance of the composite membrane was measured as follows: the permeation flux was 3472.5 gm -2 h -1 , the separation factor is 11.7, and the ethanol content in the permeate is 38wt%.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a uniform, dense, preferentially alcohol-permeable composite membrane, characterized in that: The following steps are involved: Step a, adding catalyst A containing copper ion compound into ethanol and mixing evenly, then adding monomer and organic polymer corresponding to synthetic graphyne thereto, stirring for 0.5-2h, ultrasonicating for 0.1-2h, then placing in a 50-150°C oven and heating for 2-10h to prepare graphyne / organic polymer membrane liquid A; loading membrane liquid A onto a porous base membrane by a certain method, then placing in the air to volatilize the solvent; Step b, mixing the silicon-based crosslinking agent and catalyst B in a certain proportion, stirring for 0.1-2h, and preparing a membrane liquid B; Step c, take a certain amount of membrane liquid B and place it at the bottom of the container, heat it to 40-100°C to fill the container with the cross-linking agent vapor, place the porous base membrane loaded with graphyne / organic matter in step a in the container vapor, and allow the organic matter and the cross-linking agent to react with gas-solid or / and gas-liquid on the membrane surface for 3-8 hours; then take out the membrane and place it in an 80°C environment for 0.5-8 hours for further thermal cross-linking reaction.
2. The method according to claim 1, characterized in that The graphyne described in step a is one or more of graphdiynes (GDY); the monomer corresponding to the synthesis of the above-mentioned graphyne is one or more of 1,3,5-triethynylbenzene (TEB) containing terminal alkynes, tris(4-ethynylphenyl)amine (TEPA), 1,3,5-tri-(4-ethynylphenyl)benzene (Ext-TEB) or hexaethynylbenzene (HEB); catalyst A is one or more of copper hydroxide (Cu(OH)2) or copper acetate (Cu(CH3COO)2); the organic polymer is one or more of polydimethylsiloxane (PDMS), polyphenylmethylsiloxane (PPMS), polytrifluoropropylmethylsiloxane (PTFMS) or polytrimethylsilyl propyne (PTMSP).
3. The method according to claim 1, characterized in that The porous base membrane described in step a is an organic polymer membrane, an inorganic membrane or an organic / inorganic hybrid membrane, and the average pore size is 10-100nm; the shape of the porous base membrane is flat, tubular or hollow fiber.
4. The method according to claim 1, characterized in that In step a, the content of organic polymer in the membrane liquid A is 5wt%-80wt%; the content of graphyne synthesis monomer is 0.1wt%-20wt%; and the concentration of the solution of catalyst A added to ethanol is 0.1-5g / L.
5. The method according to claim 1, characterized in that In step a, the method for loading the membrane liquid A on the porous base membrane is one or more of an immersion method, a vacuum filtration method, a spraying method, a spin coating method, and a blade coating method.
6. The method according to claim 1, characterized in that The crosslinking agent in step b is one or more of tetraethyl orthosilicate (TEOS), propyl orthosilicate (TPOS), butyl silicate (TBOS), vinyl triethoxysilane (VTES), ethyl triethoxysilane (ETES) or trifluoropropyl triethoxysilane (TFPTES); the catalyst B is one or more of dibutyltin dilaurate (DBTDL), monobutyltin oxide (MBTO), dibutyltin oxide (DBTO), tripropyltin oxide (TPTO) or chloroplatinic acid.
7. The method according to claim 1, characterized in that The content of the cross-linking agent in the membrane solution described in step b is 80wt%-99wt%, and the content of the catalyst B is 1wt%-20wt%.
8. A uniform, dense, preferentially alcohol-permeable composite membrane prepared by the method according to any one of claims 1 to 7.
9. Use of the uniform, dense, preferentially alcohol-permeable composite membrane prepared by the method according to any one of claims 1 to 7 to separate ethanol from an aqueous solution by pervaporation.
Citation Information
Patent Citations
PDMS / PVDF complex film for separating organic steam and preparation method thereof
CN101229487A
Hollow fiber composite nanofiltration membrane based on natural polymer and preparation method thereof
CN106823861A
Membrane material steam crosslinking device and control method thereof
CN109912831A
Wrinkled graphene oxide / nanofiber composite membrane and preparation method and application thereof
CN111214962A
Oil-water separation membrane and preparation method thereof
CN113750813A